Remarks by World Bank Group President David Malpass to the 52nd Washington Conference on the Americas - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass to the 52nd Washington Conference on the Americas. He discusses: the Bank forecast that Latin America and the Caribbean will grow by only 2.3 percent in 2022. Energy, food, and fertilizer prices are rising at a pace not seen in many years, hitting the region’s poor particularly hard. The commodity price boom will benefit natural resource exporters and government revenue. One key unfolding crisis is the rise of inflation in advanced economies. At the primary and secondary levels, the learning losses from the Coronavirus disease 2019 (COVID-19) lockdown policies need to be urgently addressed. As the leaders from the region gather for the Summit of the Americas in Los Angeles, it provides an opportunity to be strategic in addressing the challenges ahead.